The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1806-9282.66.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of aspirin resistance is higher in patients with acute coronary syndrome and atrial fibrillation than without atrial fibrillation

Abstract: SUMMARY In patients with atrial fibrillation, standard anticoagulation with a vitamin K antagonist plus dual antiplatelet therapy with a P2Y12 inhibitor and aspirin is the standard of care after percutaneous coronary intervention (PCI). While this therapy reduces the risk of thrombosis and stroke, it increases the risk of bleeding. It is unclear whether the antiplatelet effect of aspirin and clopidogrel may worsen atrial fibrillation (AF). OBJECTIVE Thus we aimed to analyze platelet aspirin resistance (AR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Research had shown that AR is an independent predictor of cardiovascular adverse risk (Pasala et al, 2016). In recent years, more and more studies have been conducted on AR, and the improvement of AR may become a research hot spot in the future (Xue et al, 2014;Al-Jabi, 2017;AJin et al, 2019;Baş et al, 2020).…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…Research had shown that AR is an independent predictor of cardiovascular adverse risk (Pasala et al, 2016). In recent years, more and more studies have been conducted on AR, and the improvement of AR may become a research hot spot in the future (Xue et al, 2014;Al-Jabi, 2017;AJin et al, 2019;Baş et al, 2020).…”
Section: Conclusion and Prospectivementioning
confidence: 99%